Performance Analysis of RC4 Symmetric and RSA Asymmetric Cryptographic Algorithms In Securing Normal Text Messages - Renaldi R (Al'Adzkiya, 2024)
Information security plays a crucial role in the digital age, particularly in safeguarding text messages from unauthorized access. Cryptography serves as a means of data security by employing encryption algorithms that transform the original message into a format that is hard to comprehend. This thesis examines the performance evaluation of two cryptographic algorithms: RC4, a symmetric algorithm, and RSA, an asymmetric algorithm, in the protection of regular text messages. This research centers on comparing the two algorithms regarding their encryption and decryption speeds, along with their effectiveness in masking the character frequency pattern present in the original text message. Testing was conducted with various short, medium, and long text documents. The test outcomes indicate that RC4 excels in speed for both encryption and decryption processes, particularly when handling large texts. Nonetheless, RSA excels in security due to its capacity to generate a more random and unpredictable character frequency distribution.